2010
DOI: 10.3109/00016341003623746
|View full text |Cite
|
Sign up to set email alerts
|

Infertility, mental disorders and well‐being – a nationwide survey

Abstract: Infertility was associated with mental health, especially dysthymia and anxiety. The results differed by gender and the permanency of infertility. Gender-specific psychosocial support and follow-up for infertile people is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(144 citation statements)
references
References 28 publications
6
131
2
5
Order By: Relevance
“…Fertility treatment for our participants was associated with a range of negative emotions, which is consistent with earlier literature [6] [23] [30] [31] [32]. In addition our participants described positive emotions that could occur, especially hope.…”
Section: Comparison With the Existing Literaturesupporting
confidence: 81%
“…Fertility treatment for our participants was associated with a range of negative emotions, which is consistent with earlier literature [6] [23] [30] [31] [32]. In addition our participants described positive emotions that could occur, especially hope.…”
Section: Comparison With the Existing Literaturesupporting
confidence: 81%
“…In addition, these To date, many researches showed that depression and anxiety were more frequently observed in women with infertility as compared to controls. [1][2][3][4][5][6] Matsubayashi et al reported that both scores were significantly higher in infertile women than those of pregnant women, and scores were not affected by women's work state similar to our data, however, their scores were not affected by age and duration of infertility in contrast with our data. 1 In another study infertile women were reported to have higher scores of suspicion, guilt and hostility.…”
Section: Discussioncontrasting
confidence: 57%
“…Klemetti et al mentioned that infertility was associated with mental health as the childless infertile women had intensified adjusted risk for anxiety disorders. 3 Chen at al. conducted a study on 112 participants in an assisted reproductive technique clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective [14][15][16][17] and cross-sectional [18][19][20] studies have assessed psychological functioning in men at diagnosis or immediately prior to ART treatment. In broad terms, these sought to elucidate the nature of psychological distress; whether there were differences in psychological symptoms, most commonly depression and anxiety or quality of life between men and women, whether rates of clinically significant symptoms exceeded population prevalence and whether risk factors for, or correlates of, mental health problems could be identified.…”
Section: Psychological Reactions To Infertility Diagnosesmentioning
confidence: 99%